From cosmos to cell: constructing a paradoxical selfhood through planetary and biological bodies in the poetry of Diane Ackerman and Jane Hirshfield - Tan, Jasmine Hui Jun (Nanyang Technological University, 2024)
To date, research on literature and science have favored long-form writing and this thesis seeks to remedy that by investigating the utilization of biological metaphors to construct selfhood by understudied contemporary poets Diane Ackerman and Jane Hirshfield. The research project will analyze fourteen poems by Ackerman and Hirshfield, collectively published over the span of approximately four decades and across nine different collections, focusing on poetic journeys that oscillate between material and immaterial reality, traveling into and through the body and beyond. This project’s objective is to examine Diane Ackerman and Jane Hirshfield’s use of biology to elucidate the paradoxes of selfhood whilst still maintaining a sense of mystery and wonder. I argue that Ackerman and Hirshfield construct selfhood as existing between the threshold of biological bodies and planetary bodies, ultimately underscoring two selves in their poetry: a biological self and a poetic self. Ackerman explores selfhood on a vast cosmic scale unlike Hirshfield’s depiction of selfhood which takes place on a smaller scale, within the human body. Ackerman postulates how the human self is more itself when we encounter an alien self, with the recognition of our biological similarities evidence of a cosmic selfhood. In contrast with Ackerman, Hirshfield conceives of the self through biological bodies, positing how the body both limits and expands selfhood. Unlike Ackerman, Hirshfield approaches the redefinition of the self from the inside out, reflecting how our bodies on a microcosmic level, from body to cosmos, change the way we conceive of the self on the outside. Hirshfield posits how the body both limits and expands selfhood by delineating a biological and poetic self. But despite differences in their poetics, both poets expand our understanding of selfhood with Ackerman’s cosmic kinship being the basis for a more universal kind of selfhood, one that Hirshfield also adopts by drawing parallels between the human body and more-than-human bodies. I will evaluate recurring motifs in their poetry, namely the traveling, hunger, heart, sound and sight. Both poets show that the continued search and redefinition of personal identity is crucial in the ever-evolving ecosystem of being. More than biology just being a metaphor, this poetic space or body that the poets create is one that allows selfhood’s paradoxes to be constituted through the assimilation of science into poetry. This concealment and revelation of the self through these paradoxical internal contradictions mirrors the oscillation between a wholeness and fragmentariness of the self that remains unresolved in their poetry. While Ackerman and Hirshfield’s paradoxical poetics seem to embody qualities of what Linda Hutcheon terms a ‘postmodern poetics’, this project eschews labeling them as postmodern because that would undermine this element of ‘Negative Capability’ (a term that Romantic poet John Keats coined) that both poets valorize. A key paradox of selfhood expounded upon by the poets include how a single human self is composed of multiple selves and it is a shared difference that unites separate selves, therefore expanding definitions of the self to include the cellular, bodily and cosmic.